Say, for example, in the sequence of 3, 8, 13, 18, 23, 28, and 33, the first term is 3. When solving problems involving arithmetic sequence, we can denote it as a1 = 3 ora= 3. Common difference– the common difference of an arithmetic sequence is the difference between two consecu...
Learn the Arithmetic sequence formula and meaning. Discover how to find the common difference and read arithmetic sequence examples.
Given the arithmetic sequence with a_1 = 35 and a_k+1 = a_k - 3, find: a) the common difference b) the first five terms of the arithmetic sequence c) the nth term of the sequence as a function of n. Find the indicated term for the arithmet...
The sum of the first 10terms of the sequence is 162.(a) Show that 10a+45 d =162Given also that the sixth term of the sequence is 17.(b) write down a secon d equation in a an d d,(c) fin d the value of a an d the value of d. ...
The common difference of an arithmetic sequence is 2 and the fifth term is 15. What is the first term? A. 5 B. 7 C. 9 D. 11 相关知识点: 试题来源: 解析 B。解析:设首项为 a1,根据等差数列通项公式 an = a1 + (n - 1)d,这里 a5 = 15,d = 2,n = 5,代入可得 15 = a1 +...
Common difference, d = 2 – 1 Now, we know that finding the nth term of an arithmetic sequence is given byan= a + (n − 1) × d. Substituting the given values in this equation, we have, an= 1 + ( 15 – 1 ) x 1
Arithmetic Sequences Finding the nth Term - St Anne:算术序列的第n项发现-圣安妮nn,N,序列,the,nth,term,算术序列,Term,term的,The 文档格式: .ppt 文档大小: 15.5K 文档页数: 4页 顶/踩数: 0/0 收藏人数: 0 评论次数: 0 文档热度:
The common difference in this sequence is 8 because each term is obtained by adding 8 to the previous term. The next term can be found by adding 8 to the last term, which is 35. Therefore, the next term in the sequence is 43. ...
If the first term of an arithmetic sequence is 5 and the common difference is 3, then the third term is ___. A. 11 B. 10 C. 12 D. 9 相关知识点: 试题来源: 解析 A。中文解析:首项\(a_1 = 5\),公差\(d = 3\),根据通项公式\(a_n = a_1 + (n - 1)d\),第三项\(a_...
(1)since a11=0 so a1+10d=0……(1)S14=98 so (2a1+13d)*14/2=98 so 2a1+13d=14 (2)2(1)-(2)=7d=-14 d=-2 then a1=20So that the general term of the sequence is an=22-2n(2)a1>=6a11=a1+10d>0(2a1+13d)*14/2反馈...